(untitled) (Carte Romanze, 2019)
Rileggendo la novella IV 1 secondo la paragrafatura originaria, trasmessa dal codice autografo del Decameron, ms. Hamilton 90, è possibile approfondire l’analisi critica della triste storia di Tancredi e Ghismonda, arrivando ad un’interpretazione che rispecchia l’ultima volontà d’autore. Thanks to a new reading of Decameron’s novel IV 1 based on the original paragraphs transmitted by the autograph manuscript, ms. Hamilton 90, it is possible to deepen the critical analysis of Tancredi and Ghismonda’s sad story, providing an interpretation that reflects Boccaccio’s ultimate will.